LQ45: How Volatile Are Stock Prices In The Post-Pandemic Period? - Maharani, Anantia Putri; Prayitno Utomo, Langgeng (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This research aims to analyze the effect of profitability and capital structure on the stock prices of companies included in the LQ45 index on the Indonesia Stock Exchange during the 2022–2024 period. The LQ45 index was selected because it consists of companies with high liquidity and large market capitalization that attract strong investor attention. Profitability is measured using Earnings Per Share (EPS), while capital structure is measured using the Debt to Equity Ratio (DER). Both indicators are used because they reflect a company’s ability to generate profits and manage its financing sources. This research applies a quantitative approach using secondary data obtained from annual financial statements and stock price data. The sample was determined through purposive sampling, resulting in 28 companies with a total of 84 observations. The analysis was conducted using multiple linear regression after the model satisfied the classical assumption tests. The results indicate that EPS has a positive effect on stock prices, meaning that higher earnings per share tend to be positively interpreted by investors. DER also shows a positive effect on stock prices, suggesting that, in the context of LQ45 companies, the use of debt may be perceived as a financing strategy that supports growth. Overall, these findings confirm that fundamental indicators remain important in explaining stock price movements and are relevant for investment decision-making.